Soil and Pest Management in French Polynesian Farming Systems and Drivers and Barriers for Implementation of Practices Based on Agroecological Principles - Surchat, Mélanie; Wezel, Alexander; Tolon, Vincent; Breland, Tor Arvid; Couraud, Philippe; Vian, Jean-François (Frontiers in Sustainable Food Systems, 2021)
In the context of climate change, French Polynesia is committed to increasing qualitatively and quantitatively local food production. In this regard, agroecology is perceived as a sustainable pathway to improve farming practices. This article proposes first a theoretical framework to analyze the proximity of farmers’ management to agroecological principles. Second, it describes the current use of agroecological pest and soil management practices by French Polynesian farmers. And third, it explains which agronomic and socio-economic factors drive the implementation of agroecological practices. For this, qualitative interviews were conducted with 32 farmers on three islands, and statistical analyses were carried for correlation between the use of practices and socio-economic variables. Results show that French Polynesian farmers implement different soil and pest management practices that are in line with agroecological principles. Farmers scored better in terms of pest management with high plant diversity, implementation of crop rotations, and mechanical weed management. There is a significant influence of the ‘cropping system’ and the ‘production system’ (organic, integrated, conventional) on the use of practices as well as proximity to agroecological principles. Identified pathways for an agroecological transition are implementing farmer to farmer knowledge exchange, farmer networks, and farm demonstrations as well as training of extension services staff.